Modular Leveling Program for first-year students of the University of Costa Rica of the Pacific Headquarters in the year 2022: systematization of tasks - Hernández Sánchez, Gerardo (2026)
The Modular Leveling Program for first-year students (Pre-UCR Project) is a project sponsored by the Teaching Vice-Rectory (VD) and the Pacific Headquarters Teaching Coordination (CDSP) of the University of Costa Rica (UCR) aimed at the student population that in 2022 enters the UCR for the first time. The Pre-UCR Project intends, as a purpose, to allow first-year students an early approach to UCR, as well as to offer them useful and essential tools for their future academic and professional training. Six were the areas to be taken into consideration in this project, namely: Academic Research, Soft Skills, Mathematical Skills, Reading Comprehension, Oral English and Logical Thinking. As conclusions, it is shown that in a random sample of 100 students, all of them expressed the need to continue with the project and extrapolate it to all the UCR Headquarters and Campuses. Likewise, all the respondents expressed the importance and relevance that the Modular Leveling Program for first-year students has for their future professional lives.